2023
DOI: 10.3390/cancers15051366
|View full text |Cite
|
Sign up to set email alerts
|

Rational Targets of Therapy in Extranodal NK/T-Cell Lymphoma

Abstract: Extranodal NK/T-cell lymphoma (ENKTL) is an aggressive extranodal non-Hodgkin lymphoma (NHL) with poor outcomes, particularly in advanced-stage and relapsed/refractory disease. Emerging research on molecular drivers of ENKTL lymphomagenesis by next-generation and whole genome sequencing has revealed diverse genomic mutations in multiple signaling pathways, with the identification of multiple putative targets for novel therapeutic agents. In this review, we summarize the biological underpinnings of newly-unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 159 publications
(253 reference statements)
0
5
0
Order By: Relevance
“…According to various studies, STAT3 mutations are the most commonly observed genetic alterations, followed by activating mutations in JAK3. In the treatment of ENKTL, there are multiple inhibitors available that target the JAK/STAT pathway [ 15 ]. The selective JAK3 inhibitor has recently been demonstrated to have a potent anti-tumor activity in pre-clinical study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to various studies, STAT3 mutations are the most commonly observed genetic alterations, followed by activating mutations in JAK3. In the treatment of ENKTL, there are multiple inhibitors available that target the JAK/STAT pathway [ 15 ]. The selective JAK3 inhibitor has recently been demonstrated to have a potent anti-tumor activity in pre-clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…The positive rate of PD-L1 was reported to be 39–100% in ENKTL tissues [ 16 ]. Anti-PD-1 antibodies (pembrolizumab, nivolumab, sintilimab, tislelizumab, and avelumab) have been studied in small cohorts of relapsed or refractory ENKTL, and have shown promising results [ 15 , 45 – 47 ]. The 2018 National Comprehensive Cancer Network (NCCN) guidelines recommend pembrolizumab and nivolumab for relapsed/refractory ENKTL [ 17 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell survival/proliferation pathways are frequently upregulated, including the JAK/STAT, NF-κB, RAS/MAPK and PDGFRa pathways. 118 As a rare entity, there are no prospective randomised trials to guide optimal management. Traditionally, treatment is intensive multiagent chemotherapy for advanced-stage disease and/or local radiation for limited-stage disease.…”
Section: E N K Tl Nasa L T Y Pementioning
confidence: 99%
“…BIM , TET2 , ASNS , PRDM1 , MLL2/MLL3 and BCOR ) and altered gene expression ( EZH2 overexpression), have been identified in significant minorities of cases, with epigenetic modification being the most common pathogenic mechanism of disease, suggesting potential roles for hypomethylating agents and novel miRNA inhibitors. Cell survival/proliferation pathways are frequently upregulated, including the JAK/STAT , NF‐κB , RAS/MAPK and PDGFRa pathways 118 …”
Section: Enktl Nasal Typementioning
confidence: 99%